Jezus van Nazareth. - Sölle, Dorothee 1929-2003; Schottroff, Luise; van der Vinne, Harmina (Kampen Ten Have, 2001)
Twee grote vrouwelijke theologen beschrijven in dit boek het leven van Jezus. (Bron: covertekst)